Harnessing Learners' Insight of Online Courses and Learning Management System - Hazalina Hashim; Mohammed Yusoff; Nurhizam Safie Mohd Satar (2006)
The frequency of online courses using web-based learning has continued to increase in terms of demand and access. However the effectiveness of online courses particularly in relation to individual learners’ needs, perceptions, performance and outcomes are sometimes being questioned. To support for a successful learning system, this study will harness learners’ insight of online courses and learners’ use of learning management system (LMS). Much of this study is based on learner insights of the quality and quantity of their interactions and learning experiences using LMS and social presence in online courses. Only by understanding learners’ insights can we develop strategies or guidelines for creating a more inclusive and effective LMS and online courses. This study was conducted on 224 respondents from the Faculty of Information Technology and Multimedia Communication, Open University Malaysia. This study allows for learners’ feedback and an opportunity for the institution to improve the learning system and nurture e-learning. (Authors' abstract)